2005
DOI: 10.1136/tc.2004.008755
|View full text |Cite|
|
Sign up to set email alerts
|

Smoke-free law did not affect revenue from gaming in Delaware

Abstract: Objective: To determine the effect of the Delaware smokefree law on gaming revenue. Methods: Linear regression of gaming revenue and average revenue per machine on a public policy variable, time, while controlling for economic activity and seasonal effects. Results: The linear regression showed that the smoke-free law was associated with no effect on total revenue or average revenue per machine. Conclusion: Smoke-free laws are associated with no change in gaming revenue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 6 publications
(3 reference statements)
2
37
0
Order By: Relevance
“…Two previous studies from the United States have analysed the impact of smoke-free policies on gaming machine expenditure and the conclusions were mixed. Mandel et al 3 found no significant effect of the smoke-free law in three gambling venues in Delaware, USA; however, Pakko4 found a significant decrease in revenue when analysing the same data but with different model specifications. Another study from the United States found no effect of the smoke-free policy on profits from bingo and charitable gaming in Massachusetts, USA 5…”
mentioning
confidence: 96%
“…Two previous studies from the United States have analysed the impact of smoke-free policies on gaming machine expenditure and the conclusions were mixed. Mandel et al 3 found no significant effect of the smoke-free law in three gambling venues in Delaware, USA; however, Pakko4 found a significant decrease in revenue when analysing the same data but with different model specifications. Another study from the United States found no effect of the smoke-free policy on profits from bingo and charitable gaming in Massachusetts, USA 5…”
mentioning
confidence: 96%
“…See also the 'Erratum' subsequently published in Tobacco Control(Glantz and Alamar, 2005). 2 Losses associated with the Delaware smoke-free law are also suggested by Dover Downs (2004a, b) andMarcel (2004).Applied Economics ISSN 0003-6846 print/ISSN 1466-4283 online ß 2008 Taylor & Francis…”
mentioning
confidence: 82%
“…6 The trend terms are based on the variable TIME, specified as t*100. As cited by Mandel et al (2005), the inclusion of a quadratic trend specification is intended to account for the slowdown naturally associated with the maturing of the industry after a period of rapid initial growth; moreover, it is supported by the data. 7 The number of terminals is limited by Delaware law, providing a degree of exogeneity to this supply-side variable.…”
Section: Regression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the US, there was an intense debate about the economic impacts of the smoking ban in New Jersey in November 2002 (Mandel et al, 2005;Pakko, 2008;Pakko, 2006;Thalheimer and Ali, 2008). Studies of the Illinois smoking ban of 2008 found that the revenue decline of Illinois casinos after 2008 was due to a coincidence of economic recession (Harris et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%